THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT AND PSYCHOLOGICAL EMPOWERMENT ON WORK ENGAGEMENT IN GENERATION Z EMPLOYEES - Khoirunnisa Virgiana Khan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Generation Z employees are starting to dominate the world of work and become a challenge for companies because this generation has characteristics such as liking flexibility, having a high desire to change jobs and minimal effort at work. This shows that generation Z employees have low work engagement. The purpose of this study was to test empirically the effect of perceived organizational support and psychological empowerment on work engagement in Generation Z employees. This research was conducted on 102 respondents with certain criteria, namely employees who work in private companies, aged 18-28 years and have been working for at least 1 year in the current company. Data collection was carried out by the Utrecht Work Engagement Scale (UWES-17), the Scale of Perceived Organizational Support (SPOS), and the Psychological Empowerment scale. The data analysis technique used to test the hypothesis in this study is multiple linear regression. Based on the results of data analysis, an F value of 72.227 was obtained with a significance value of 0.000 (p<0.01) and value R square of 0.593. This shows that there is a very significant effect of perceived organizational support and psychological empowerment on work engagement in generation Z employees. Perceived organizational support and psychological empowerment contribute work engagement of 59.3% while the remaining 40.7% is contribute by other factors outside of research. Meanwhile, it is partially known that perceived organizational support contribute 38.4% and psychological empowerment of 45.8% on work engagement.